Early Embryonic Mortality in Bovines: Current Insights and Interventions - Kumar Sahu, Uttam; Kumar, Amit; Kumar, Brijesh; Kumar Patra, Manas; Khan, Meraj (Animal Reproduction Update, 2025)
Early embryonic mortality (EEM) is a critical reproductive challenge in bovines, significantly impacting fertility, milk production, and farm economics. Despite high fertilization rates, embryonic losses during the first 24 days of gestation remain a major bottleneck in achieving optimal conception rates. This review synthesizes current understanding of the multifactorial aetiology of EEM, encompassing genetic, endocrine, immunological, nutritional, environmental, and managerial factors. Species, breed, age, parity, milk yield, and stress are all associated with increased embryonic loss. Endocrine disruptions such as luteal phase defects and inadequate progesterone levels are frequently implicated. Immune system dysfunction, including maternal fetal immunological incompatibility and subclinical infections, further compromises embryo viability. Diagnostic tools such as early pregnancy factor, preimplantation factor, progesterone assays, ultrasonography, and pregnancy-associated glycoproteins (PAGs) allow early detection of EEM. Therapeutic interventions include hormonal supplementation (GnRH, hCG, progesterone, kisspeptin), immunomodulators, endometrial receptor modulators, and nutritional strategies such as omega-3 fatty acid supplementation and insulin-based regimens. Assisted reproductive technologies like embryo transfer and embryo co-transfer offer promising alternatives for repeat breeder animals. Preventive strategies emphasize precise AI timing, estrus detection, heat stress mitigation, and improved nutritional management to enhance uterine receptivity and embryo survival. This review underscores the need for integrated, individualized approaches to managing EEM, combining diagnostics with targeted therapeutic and environmental interventions. Future research directions include identifying novel biomarkers, refining genomic selection for fertility traits, and leveraging AI-based tools for real-time reproductive monitoring. A comprehensive understanding of EEM pathophysiology, coupled with evidence-based interventions, is essential to improve reproductive efficiency and sustainability in dairy production systems.